2012
DOI: 10.1186/1471-2393-12-47
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia complicated by advanced maternal age: a registry-based study on primiparous women in Finland 1997–2008

Abstract: BackgroundPreeclampsia is a frequent syndrome and its cause has been linked to multiple factors, making prevention of the syndrome a continuous challenge. One of the suggested risk factors for preeclampsia is advanced maternal age. In the Western countries, maternal age at first delivery has been steadily increasing, yet few studies have examined women of advanced maternal age with preeclampsia. The purpose of this registry-based study was to compare the obstetric outcomes in primiparous and preeclamptic women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
145
6
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(188 citation statements)
references
References 28 publications
22
145
6
15
Order By: Relevance
“…We found that pre eclampsia is 4 times likely if a woman was pregnant before 20y of age. A similar retrospective study done in Finland also concluded with the same result [13]. This might either be due to the age itself or may be due to inadequate antenatal care given to a teenage pregnant girl.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…We found that pre eclampsia is 4 times likely if a woman was pregnant before 20y of age. A similar retrospective study done in Finland also concluded with the same result [13]. This might either be due to the age itself or may be due to inadequate antenatal care given to a teenage pregnant girl.…”
Section: Resultssupporting
confidence: 58%
“…This has been conclusively found in various studies [13,15], but the incidence of pre eclampsia in women less than 20y of age is an area that has not been given much importance. Nulliparity is associated with increased risk of pre -eclampsia and eclampsia by two folds.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Advanced maternal age is an independent risk factor for adverse outcomes in first-time mothers with preeclampsia. 8,9 Mean gestational age in severe preeclamptic group was significantly lower than normotensive group indicating an inhomogenous distribution in research samples. This result was in accordance with a study by Zhang et al 7 which found that mean gestasional age in severe preeclamptic group was significantly lower than control group.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, in univariate analysis, we found that smoking until birth was associated with advanced maternal age (Table 3). Pregnant women aged older than 35 years are considered to be at a higher risk for adverse perinatal outcomes (12,13). Smoking during pregnancy for this age group could add burden and worsen adverse perinatal outcomes (11).…”
Section: Discussionmentioning
confidence: 99%